CORRELATIONS BETWEEN FAMILY SUPPORT AND COMPLIANCE LEVELS UNDERGOING INDEPENDENT ISOLATION AS AN EFFORT FOR COVID-19 RECOVERY IN THE WORK AREA OF THE PERWIRA HEALTH CENTER IN 2022 - Uji Awaludin; Rotua Suriany, Dinda Nur Fajri; Rotua Suriany (Jurnal Medicare, 2023)
Background: quarantine patients must comply with health protocols. If you don't comply, you can transmit the virus, the isolation period will be longer and the situation will get worse. 211 people who do self-isolation in RW 13 Kelurahan officer. The problem found was in the form of transmission from the accompanying family due to the lack of implementing Health protocols. Family moral or material support is useful so that the patient is not lonely, accepting, enthusiastic and optimistic that he can recover. Good family support can affect the readiness of Covid-19 patients during quarantine so that patients are disciplined. Methods: This study is a quantitative analytical observational study with a cross-sectional approach and purposive sampling technique and uses direct and online questionnaires via googleform to 69 respondents in RT 002, 003, and 008. The chi square test was used to determine the existence of a correlations. Results: Based on the results of the Chi Square test analysis, the p value = 0.000 was obtained. This means that H0 is rejected and H1 is accepted. Conclusion: There is a correlations between family support and the level of compliance with self-isolation in the work area of ​​the Perwira Health Center in 2022.